Kajian Pelaksanaan Gerakan Tanam Jagung Panen Sapi (TJPS) Dalam Meningkatkan Nilai Tukar Petani (NTP) Di Desa Manusak, Kabupaten Kupang, Provinsi Nusa Tenggara Timur - Meryanto Yonatris Tana; Marthen Robinson Pellokila; Maria Indryani Hewe Tiwu (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
Corn and cattle are the main commodities in dry land farming in East Nusa Tenggara (NTT), with corn as a food source and cattle as a source of income. This province has vast dry land potential, namely 1,734,488 H, but its utilization is still less than optimal. The Cattle Harvest Corn Planting Program (TJPS) was launched to increase corn production, cattle population and farmer welfare.This research analyzes the Farmer Exchange Rate (NTP) in Manusak Village, Kupang Regency, and the factors that influence it, as well as examining government policies in supporting the efficiency of the corn-cattle farming system. Qualitative methods through interviews, observations and text analysis are used to understand farmers' experiences in farming.The results show that the NTP in the Gacinda and Leselik farmer groups is different: Gacinda has a higher NTP than Leselik, which is caused by differences in corn production costs and yields. In conclusion, corn productivity and costs incurred affect farmer welfare, with high expenditures potentially reducing NTP.